2018
DOI: 10.1001/jamasurg.2018.0979
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Changes in Body Composition and Neoadjuvant Treatment for Pancreatic Cancer

Abstract: Patients with PC experience a significant loss of adipose tissue during neoadjuvant chemotherapy, but no muscle wasting. An increase in muscle tissue during NT is associated with resectability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
95
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 35 publications
3
95
1
1
Order By: Relevance
“…Treatment-associated toxicity in these patients may be the result of improper drug dosing regimens that are based on antiquated methodology (18). Recent clinical evidence suggests the use of body composition measurement to improve drug dosing, reduce toxicity, and establish early intervention in patients with cancer (7, 9). Therefore, we conclude that the use of DEXA as a tool to characterize SMW to improve dosing is an area that warrants further study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Treatment-associated toxicity in these patients may be the result of improper drug dosing regimens that are based on antiquated methodology (18). Recent clinical evidence suggests the use of body composition measurement to improve drug dosing, reduce toxicity, and establish early intervention in patients with cancer (7, 9). Therefore, we conclude that the use of DEXA as a tool to characterize SMW to improve dosing is an area that warrants further study.…”
Section: Discussionmentioning
confidence: 99%
“…This study concluded that survival in sarcopenic patients was 1/3 of their non-sarcopenic counterparts, regardless of body weight. In addition, increases in lean mass during neoadjuvant treatment (NAT) has been shown to be independently associated with progression to resection surgery in patients with PDAC (9), even when these patients experienced loss of adipose tissue. Notably, patients who experienced decreases in lean mass during or after NAT underwent surgical exploration, but not resection.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations